2023
DOI: 10.19171/uefad.1189899
|View full text |Cite
|
Sign up to set email alerts
|

Music Teacher Candidates’ Attitudes Toward Distance Instrument Education

Abstract: Araştırmada müzik öğretmeni adaylarının bazı değişkenlere göre uzaktan çalgı eğitimine yönelik tutumlarının incelenmesi amaçlanmıştır. Araştırmanın örneklemini 2020-2021 eğitim öğretim yılı güz yarıyılında yedi üniversitesinin Eğitim Fakültesi Güzel Sanatlar Eğitimi Bölümü Müzik Eğitimi Ana Bilim Dallarında öğrenim gören 240 öğrenci oluşturmuştur. Genel tarama modeli kullanılan araştırmada veriler Kişisel Bilgi Formu, Uzaktan Eğitime Yönelik Tutum Ölçeğinin araştırmacılar tarafından uzaktan çalgı eğitimine uya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Additionally, it was found that the preferred device did not significantly affect the general attitude toward E-learning (Table 6). Reviewing the literature, it can be observed that Acar and Egilmez's (2023) study on pre-service music teachers also reported a lack of significant differences based on the preferred/used device variable in E-learning environments. The similarity in the levels of general attitudes toward E-learning and the absence of significant differences can be associated with the fact that in today's technology landscape, mobile phones and computers do not exhibit significant differences in terms of hardware or it can be linked to the similarity in the Elearning systems preferred/developed by universities.…”
Section: E-lerning Attitude Of Teacher Candidates In Online Learning ...mentioning
confidence: 99%
“…Additionally, it was found that the preferred device did not significantly affect the general attitude toward E-learning (Table 6). Reviewing the literature, it can be observed that Acar and Egilmez's (2023) study on pre-service music teachers also reported a lack of significant differences based on the preferred/used device variable in E-learning environments. The similarity in the levels of general attitudes toward E-learning and the absence of significant differences can be associated with the fact that in today's technology landscape, mobile phones and computers do not exhibit significant differences in terms of hardware or it can be linked to the similarity in the Elearning systems preferred/developed by universities.…”
Section: E-lerning Attitude Of Teacher Candidates In Online Learning ...mentioning
confidence: 99%